Caracterização das unidades sísmicas, processos sedimentares e idade do cânion Almirante Câmara, bacia de Campos - Pellizzon, Marcela Marques (2008)
The Campos Basin is characterized by the presence of features that indicate sedimentary processes of large proportions, whether caused by gravitational flows, bottom currents or tectonics. These features are observed in the ocean floor as well along the geologic column and can be use in sedimentary processes identification. The main sedimentary processes occurring during the establishment and evolution of the Almirante Camara submarine canyon were identified using seismic lines. Interpretation of these lines allowed mapping the main reflectors and division of sedimentary package in seismic units. The units were correlated with depositional sequences observed by other authors in this basin. Five seismic units separated by unconformities were identified in the continental slope and among these unconformities were the Marco Cinza. The area of the lobe in which the canyon is located was divided in 4 different sections that can be distinguished by theirs seismic signature. In the slope it was evident the occurrence of mass wasting/mobilization. In the upper slope the reflectors are, frequently, inexistent due to the presence of intense faulting. In the middle slope the sedimentary package is well preserved and it is possible identification of main units and reflectors. This package is interpreted as progradacional due to intense flux of terrigenous sediments causing canyon overflow and vertical aggradation of the whole system. It is here proposed that the construction of this canyon has started after an erosive event that may have happened in the Eocen-Oligocen limit.